The Dissolution of Double Holliday Junctions - Bizard, Anna H. (Cold Spring Harbor Laboratory Press, 2014)
Double Holliday junctions (dHJS) are important intermediates of homologous recombination. The separate junctions can each be cleaved by DNA structure-selective endonucleases known as Holliday junction resolvases. Alternatively, double Holliday junctions can be processed by a reaction known as “double Holliday junction dissolution.” This reaction requires the cooperative action of a so-called “dissolvasome” comprising a Holliday junction branch migration enzyme (Sgs1/BLM RecQ helicase) and a type IA topoisomerase (Top3/TopoIIIα) in complex with its OB (oligonucleotide/oligosaccharide binding) fold containing accessory factor (Rmi1). This review details our current knowledge of the dissolution process and the players involved in catalyzing this mechanistically complex means of completing homologous recombination reactions.